Implementasi Jaringan LAN dan WLAN pada Mikrotik: (Studi Kasus Laboratorium Jaringan Komputer UIN Suska Riau) - Saputra, Haris Tri; Rometdo Muzawi; Rahmad Kurniawan; Teguh Sujana; Evfi Mahdiyah (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
In today's digital age, the existence of computer networks has become a crucial necessity for various institutions and organizations. Local Area Networks (LANs) and Wireless Local Area Networks (WLANs) are commonly used network infrastructures that support connectivity and information exchange between devices. MikroTik, as one of the network device providers, offers reliable solutions for managing LAN and WLAN networks. With its reputation as a leading network device provider, MikroTik is attracting attention as a potential choice to meet these needs. Additionally, the successful implementation of LAN and WLAN networks on MikroTik can provide practical guidance for organizations currently considering or planning to upgrade their network infrastructure. The focus of this research is the Computer Network Laboratory at UIN Suska Riau, where the effectiveness and efficiency of MikroTik routers and access points are evaluated in a real-world educational environment. This study begins with an overview of MikroTik technology, emphasizing its role in creating a robust and scalable network infrastructure. Furthermore, this research delves into the specific requirements and challenges faced by the Computer Network Laboratory, providing insights into the need for LAN and WLAN integration for seamless connectivity. With a better understanding of MikroTik's potential, it is hoped that the organization's information technology foundation can be strengthened and competitiveness increased in this digital era.